(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The first work on the production of synthesis gas by converting methane to carbon dioxide was published in 1928 [5]. In the 1990s, research on the conversion of carbon dioxide to methane was focused on the production of synthesis gas in various H2/CO ratios for the synthesis of hydrocarbons and petroleum products [18]. The main goal of the research of the NCM was to develop active catalysts that can work for a long time without renewal. In [16, 19], the catalytic activity of some metals (Cu, Fe, Co, Ni, Ru, Ru, Rh, Ir or Pt) was increased by using additives (Al2O3, SiC>2, TiCl, MgO, C, ZnO,SiC,BaO,ZrCl,GeO2 or zeolites) [5]. Precious metal catalysts are more resistant to coke production, but due to their high cost and limited efficiency, they are used for economical purposes.